The Role and Position of Women in the Novel Wigati: Lintang Manik Woro by Khilma Anis - Kharisma Nur Afni; Robert Rizki Yono; Nurchalistiani Budiana (CV. Rayyan Dwi Bharata, 2024)
Role is a form of responsibility related to a person's status. Meanwhile, position is a person's position both in the family and society. This research aims to determine the depiction of the role and position of women in the novel Wigati: Lintang Manik Woro by Khilma Anis. This research focuses on the role and position of women which results in gender inequality. The form of research used in this research is descriptive qualitative using a feminist approach. The data collection techniques used were reading techniques and note-taking techniques with data sources in the form of words, sentences and fragments of speech which were thought to contain the role and position of women. The results of the research are a description of the role and position of women which has been analyzed using a feminist approach.